The effectiveness of using the 1Bestarinet project toward teaching Science subject in SK Bulan Jeragam, Sebuyau, Sarawak / Mohd Reduan Patah - Patah, Mohd Reduan (2016)
Technology is evolving in line with the passage of time and we cannot run any of the changes in technology that is constantly evolving. Technology has helped people in various fields such as education, medicine, transportation, weather and much more. In the field of technology education helps in managing the governance aspects of the documentation, or even learning and teaching activities. All parties to the highest in the Ministry of Education as well as students and parents are equally affected by runoff from the development of this technology. SK Bulan Jeragam was established in 1964 and the researcher started serving this school in 2009. After five decades various changes can be seen in terms of facilities and infrastructure improvements which are compiled by the Ministry of Education, Federal Government or even State Government. For this action research the researcher has used quantitative methodology to complete the action research. In the qualitative method the researcher used the questionnaires. The questionnaires consist of 20 questions which are divided into three sections which are Section A for demography of respondents, Section B to identify the effectiveness using IBestariNet and Section C to identify the problem faced in using IBestariNet. According to the data than has been analyzed, researcher can state that this IBestariNet help the pupils a lots but at the same the problem burden from them to used it maximum as their can to get new knowledge and experience every day. The parties concerned and responsible should act more aggressively to ensure the success and the main objective of IBestariNet in helping pupils and schools in developing and producing highly educated human capital consistent with the national aspiration to become a developed nation by 2020.